Mycoplankton in river-lake water systems with different pollution. Do lakes act as traps for river mycoplankton? - Anna Pietryczuk; Jakub Korpacz; Magdalena Świsłocka; Agata Jabłońska-Trypuć; Adam Więcko; Izabela Dobrzyńska; Józefa Wiater; Adam Cudowski (Desalination and Water Treatment)
The aim of the study was to determine the abundance and species diversity of mycoplankton in lotic and lentic waters within the Rospuda river-lake system. Additionally, it aimed to explain the influence of lake waters on the abundance and species diversity of mycoplankton in the riverine sections of the river-lake system. Water samples were collected using a Limnosa sampler during the summer seasons from 2019 to 2023 from surface layers of the entire Rospuda river-lake system, which has a total length of 102 km. Sampling included 10 lakes, of which four are mesotrophic, five are eutrophic, and one is at the boundary between mesotrophy and eutrophy, as well as 11 samples from the riverine sections of the studied system. The mycoplankton abundance in the studied system ranged from 8400 to 16,400 CFU/mL, with the lowest values found in limnic waters and the highest in riverine sections. The lakes Okrągłe, Bolesty, Sumowo, and Rospuda Augustowska, which are eutrophic, exhibited the lowest species diversity of mycoplankton. The highest species diversity was observed in the river sections connecting Długie and Garbaś Lakes (Rospuda River 4) and Głębokie and Sumowo Lakes (Rospuda River 6), with 8 and 7 fungal species in the water column, respectively. The most frequently occurring fungal species in the studied system were Penicillium chrysogenum and Penicillium commune, with as much as 43 % of the identified aquatic fungi being potential pathogens, representing mycological micro-contaminants of the water.The results indicate that aquatic fungi can be valuable indicators of pollution levels and the sanitary quality of waters. This study demonstrated that the species diversity and abundance of fungi in lentic waters primarily depend on the concentration of organic matter, phytoplankton biomass indicated by chlorophyll a concentration, and the degree of water pollution. Furthermore, mesotrophic lakes contributed to an increase in mycoplankton abundance in the riverine sections, while eutrophic lakes caused a decrease in the abundance of these microorganisms in flowing waters. Therefore, it can be conclusively stated that eutrophic lakes act as traps for river mycoplankton, whereas mesotrophic lakes are sources of aquatic fungi in rivers.